APPLYING A MULTIMEDIA ONLINE MODULE TO INCREASE STUDENTS’ ACHIEVEMENT IN LEARNING ENGLISH IN A BLENDED LEARNING ENVIRONMENT - Rohaniatul Makniyah (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2022)
This study examined the application of a multimedia online module to facilitate blended learning during the post Covid-19 pandemic. As the government's policy gradually changed, that teaching and learning may take place in schools for fifty percent and other fifty percent online, learning English became blended, online and offline. This study aims at finding an alternative to increase students’ achievement by applying a multimedia online module in a blended learning environment. 38 learners of grade XI of MAN 1 Kota Tangerang participated in this study. This study employs an action research method. The data were taken from online activities in the Google Classroom, questionnaires and tests. The study found that the multimedia online module made it possible for blended learning to be facilitated as it helped learners to engage in learning activities during the teachers’ absence before them. Their learning achievement is also significantly increased. Still, the multimedia-online modules enable them to experience more than just limited real classroom situations since the multimedia online modules made it possible for them to explore various useful learning resources from various different sources, in various formats, at their own pace and time.